Elaboração e caracterização de compósitos poliméricos com o uso de Attalea speciosa Mart. ex Spreng e outras matrizes naturais - LOPES, Ilmar Alves (2019)
The Contemporary Society lives with the persistence of synthetic plastics in its post environmental compartments, causing negative impacts on biota and humans. Initiatives have emerged in order to solve the problem. One is the introduction of biopolymers or natural plastics from renewable sources. Research seeks to reconcile low cost, degradability and try to get closer to mechanical properties of synthetic plastics. The study presented here makes use of matrices with these characteristics, by using the fruit of the babassu palm Attalea Speciosa Mart. ex Spreng), of wide occurrence in the State of Maranhão. In the first article the incorporation of the fruit mesocarp (BCM) with matrices from plant and animal sources. Tests were performed using pectin (P) and whey protein concentrate (WPC) formulations making use of glycerol as plasticizer and calcium chloride dihydrate as crosslinker. The selected films remain consistent, homogeneous and flexible with a low tendency to leach and solubilize in the tests performed. In the second article, the production of biopolymers using BCM, pectin and glycerol using a Rotational Central Compound-DCCR. The films showed good properties mainly after the second crosslinking. Tests have shown that BCM contributes positively to the closure of polymer chains, making films less hydrophilic. In the third article was studying the elaboration of biopolymers based of BCM and alginate. These films have shown promise in producing bio thermoplastics. With the combinations of these natural matrices, formulations with a view the analytical interpretation of morphology by microscopy, thermal analysis, analysis of molecular arrangements and mechanical testing. The results showed that the products generated had similar characteristics, with the possibility of although with some limitations compared to synthetic polymers. The tests performed showed good mechanical properties (films with tensile strength of 226.673MPa) and low solubility (films with solubility of 4.170%). The effectiveness of crosslinking methodologies in the compaction and improvement of solubility, moisture and leaching properties in general. These results showed the possibility of using babassu mesocarp as a raw material for obtaining biopolymers. The use of babassu coconut mesocarp can also contribute to adding more value to the babassu production chain, positively impacting social development and environmental preservation because it is of products with degradation time of a few weeks when disposed in the environment.